Study on Ecology of zooplankton profusion in Bhoj wetland, India - Priyanka A. Kapoor (Advances in Aquaculture and Fisheries Management, 2015)
The influence of physicochemical properties of wetland, on its zooplankton composition and abundance were investigated for two years between February 2008 and January 2010. In both the years, total of 62 species of zooplankton were identified. At all the stations of the water body Rotifera recorded the highest percentage of 45% followed by cladocera (29%), Protozoa (13%), Copepoda and Ostracoda (8 and 4%) respectively. In terms of density, total zooplanktonic density during 1st year was 7395 Ind.l-1 that increased to 8543 Ind.l-1 in the 2nd year. In the first year, Copepoda (2 Ind.1-1 to 2415 Ind.1-1) constituted the largest group making up 63.41% of the zooplankton population density, this was followed by Cladocera (21.27%) with having numerical density ranges between (3 Ind.1-1 to546 Ind.1-1) and Rotifera group (14.15%) having a density varied from 2 to 207 Ind.1-1. The genus Bosmina (34.7%) dominated the Cladoceran group and Polyarthra and Brachionus (19.8 and 18.7%) recorded highest in terms of percentage among the Rotifera group, while as the genus Cyclops (51.5%) recorded the highest number among the Copepoda group and was also dominant genus among the zooplankton genera. During second year of study period, the Copepoda (70.08%) which had a density variation between 2 Ind.1-1 to 4491 Ind.1-1 and this was followed by Cladocera (18.67%) with numerical density ranges between 3 to 337 Ind.1-1 and Rotifera (9.08%) having density between 2 Ind.1-1 to 171 Ind.1-1. The genus Chydorus (21.1%) dominated the Cladoceran group and genus Lecane (22.0%) recorded highest in terms of percentage among the Rotifera group, while as the genus Cyclops (75.0%) recorded the highest number among the Copepoda group and was also dominant genus among the zooplankton genera. The water body is receiving domestic discharge leading to large amount of nutrient inputs and high amount of phosphate and nitrate in the water body indicates that water is eutrophic in nature.